Answer:
when x = 4, y = - 6
Step-by-step explanation:
First, the expression for the statement y varies inversely with x, can be written as:
y ∝ [tex]\frac{1}{x}[/tex], and this can also be written in an equation form as: [tex]y = \frac{k}{x}[/tex]
where k = proportionality constant relating x and y.
Next we are told that: x =-3 when y = 8. and this can be written as:
[tex]8 = \frac{k}{-3}[/tex]
finding the value of k, we cross-multiply to obtain the following:
k = -3 × 8 = -24
Finally, finding y when x = 4;
[tex]y = \frac{k}{x}[/tex]
[tex]y = \frac{k}{4}[/tex] where k = -24
∴ [tex]y = \frac{-24}{4}[/tex]
[tex]y = -6[/tex]
Therefore, when x = 4, y = - 6